2021
DOI: 10.2478/eko-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the State of Soil’s Microbial Community in Condition of Intensive Influence of Pollutants

Abstract: This paper presents the study of toxicological state of the soil. It shows ecological and microbiological properties of the soil mantle in the areas of technological environmental impact and evaluates changes in the number of soil microorganisms as a result of toxic contamination of urban soil at different distances from the Moscow loop highway, and also as a result of dumping aluminum foundry slag in Orel region. Soil-inhabiting invertebrates species composition was evaluated at different soil contamination c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…The relationship between ammonia removal and increase in surface area for microbial growth suggested that T 5 was best design for treatment performance. Microbial removal pathways, particularly nitrification, are mediated by fixed biofilms that occur on solid surfaces such as bed sediment, plant roots, and floating mats (Boltz et al, 2017;Stepanova et al, 2021). The results are broadly comparable with the findings obtained by Stewart et al (2008).…”
Section: Discussionsupporting
confidence: 73%
“…The relationship between ammonia removal and increase in surface area for microbial growth suggested that T 5 was best design for treatment performance. Microbial removal pathways, particularly nitrification, are mediated by fixed biofilms that occur on solid surfaces such as bed sediment, plant roots, and floating mats (Boltz et al, 2017;Stepanova et al, 2021). The results are broadly comparable with the findings obtained by Stewart et al (2008).…”
Section: Discussionsupporting
confidence: 73%
“…The presence of heavy metals in the environment is significantly influenced by anthropogenic activities, leading to contamination across various environmental components. Major sources of heavy metal contamination include industrial processes, mining, vehicle emissions, agricultural practices, wastewater discharge, and urban runoff (Stepanova et al, 2021;Shimod et al, 2022). These activities result in the release of heavy metals into the environment, leading to contamination of soil, sediments, water, and biota (Younis et al, 2018;Imlani et al, 2022).…”
Section: Sources Of Heavy Metal Contaminationmentioning
confidence: 99%